Technical management for the performing arts : utilizing time, talent, and money - Shanda, Mark; Dorn, Dennis (Focal Press, 2016)
Technical Management for the Performing Arts: Utilizing Time, Talent, and Money is a comprehensive guide to the tools and strategies of a successful technical manager. This book demonstrates how you can coordinate personnel, raw materials, and venues, all while keeping a production on a tight schedule and within budget. From concept to realization, through nightly performances, Technical Management for the Performing Arts focuses on the technical and organization skills a technical manager must demonstrate, and emphasizes the need for creativity and interpersonal management of a team.